Effect of rear wall inclination on cavity acoustic characteristics at high Mach numbers. Issue 1 (1st April 2022) - Tang, Yin; Luo, Lei; Zhang, Peihong; Ma, Mingsheng
Abstract: Cavity flow has been a research hotspot in aerodynamics. Cavities with low Mach numbers have been extensively investigated, while those with high Mach numbers have been less explored. In this study, a flow control method specific to the acoustic characteristics of an open-type cavity with a high Mach number was studied through the improved delayed detached eddy simulation (IDDES). Next, the rear wall of the cavity was inclined to mitigate the impact strength formed by the airflow on the rear wall surface, thus reaching the goal of reducing the aerodynamic noise in the cavity. The Mach number and length-to-depth ratio of the cavity were calculated as 3.51 and 4.5, respectively. The calculation results manifested that under a high Mach number, the sound pressure level (SPL) at the bottom of the cavity and that at its front wall surface could be obviously reduced by inclining the rear wall, and the reduction amplitude increased with the increase in the inclination angle. At the inclination angle of 60°, the SPL at the bottom could be reduced by 24 dB at maximum.